Виды Caspia и Turricaspia (Gastropoda, Pectinibranchia, Pyrgulidae) Азово-Черноморского бассейна - Алексеенко, Т.Л.; Старобогатов, Я.И. (Вестник зоологии, 1987)
The comparison of materials representing Caspia and Turricaspia species from Azov — Black Sea basin and phaseolinic clay of the Black Sea with type specimens of the nominal taxa or with illustrations in original descriptions allowed correcting and completing the list of the included species. All the Ponto-Azovian Caspia species belong to the subgenus Clathrocaspia. The following new species, new combinations and corrections are introduced into Pyrgulidae species: C. valkanovi valkanovi, C. makarovi aluschtensis, C. gmelinii stanislavi ssp. n., Turricaspia conus lindholmiana. T. bogensis (=T. pseudotriton), T. meneghiniana ukrainica ssp. n., T. grigorievi sp. n., T. chersonica sp. n., T. abichi phaseolinica S t a r o b o g a t o v, ssp. n. (=T. kolesnikoviana from the Black Sea), T. lirata marisnigrl S t a r b o b o g a t o v, ssp. n. (=T. elegantula form the Blakc Sea). Lectotypes of T. caspia and T. tritton are deasignated. The presence of T. martensii int the Azov — Balck Sea basin is established. Data on population density, biomass and frequency of Pyrguliade in the Dnieper delta and Dnieper — Bug estuary are given.